Production of Thermostable Bioflocculant from Bacillus subtilis and Optimization of Flocculation Conditions - Sabah Auhim, Husam (University of Thi-Qar Journal, 2025)
Bacteria strain H7, which produces flocculating substances, was isolated from the soil of corn field at the College of Agriculture in Abu-Ghrib/Iraq, and identified as Bacillus subtilis by its biochemical /physiological characteristics. The biochemical analysis of the partially purified bioflocculant revealed that it was a proteoglycan composed of 93.2 % carbohydrate and 6.1 % protein. The effects of bioflocculant dosage, temperature, pH, and different salts on the flocculation activity were evaluated. The maximum flocculation activity was observed at an optimum bioflocculant dosage of 0.2 mL /10 mL (49.6%). The bioflocculant had strong thermal stability within the range of 30-80 °C, and the flocculating activity was over 50 %. The bioflocculant had the highest flocculating activity at alkaline conditions pH 10 (71%), and when many salts were used as cations, ZnSO4.7H2O, MnCl2, and CuSO4 enhanced flocculation activity at 89%, 80%, and 73% respectively.